Elucidating the anti‐Staphylococcus aureus antibody response by immunoproteomics. Issue 9 (October 2016) - Stentzel, Sebastian; Gläser, Regine; Bröker, Barbara M.
Abstract : Staphylococcus aureus is a notorious pathogen both in‐ and outside hospitals as well as a frequent colonizer in healthy individuals. Immunoproteomics techniques have been employed to shed light on the human adaptive immune response to S. aureus in health and disease. Since priming of immune memory, a key property of the adaptive immune system, is the basis of successful vaccination, immunoproteomics holds promise for paving the way to an effective S. aureus vaccine.